Voltage regulation and phase quantity increase of two high-power 12-phase rectifiers - Valery Safonov; Mikhail Dziuba (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this article, we present a new method of simultaneously increasing the phase quantity and regulating the rectified voltage for two 12-phase high-power rectifiers operating at a common load. Self-excited voltage inverters separately form the necessary voltages for voltage regulation and for increasing the phase quantity. The formed voltage is input with the help of a common booster transformer. Separating the inverters functions and using the common booster transformer makes it possible to reduce the installed power of the equipment significantly compared to similar circuits when the regulation range of the rectified voltage is up to 5%. Calculations show that the inverter power for increasing the phase quantity is about 3% of the rectifier power. The circuit was modeled in MatLab/Simulink and the electromagnetic processes in the rectifier were studied. The proposed method makes it possible to reduce the total harmonic distortion of the network current and the pulsation coefficient of the rectified voltage to the values typical for 24-phase rectifiers.